Inferior Vena Cava Collapsibility as a Predictor of Mortality in Patients Admitted with Severe Acute Decompensated Heart Failure - Akhtaruzzaman, Muhammed; Ahamed, Monir Uddin; Arafat, Mohammad Ali; Haq, Arman Ibne; Hasan, Mahmud Javed; Manju, Ashek Mahmud; Haque, Amdadul (Community Based Medical Journal, 2026)
Severe acute decompensated heart failure (ADHF) has a high mortality risk. Reliable, early prognostic tools are crucial. The predictive value of inferior vena cava (IVC) collapsibility, a non-invasive measure of volume status, for in-hospital mortality in specific populations, especially in resource-limited settings, requires further validation. Our objective was to evaluate whether bedside ultrasonographic assessment of IVC collapsibility index (IVC-CI) at admission is a significant predictor of in-hospital mortality among patients with severe ADHF. A prospective cohort study was conducted at Bangladesh Medical College Hospital from January 2024 to June 2025. Using purposive sampling, 80 consecutive patients admitted with severe ADHF were enrolled. IVC-CI was measured via transthoracic echocardiography within 24 hours of admission. Data were analyzed using SPSS version 23.0, employing receiver operating characteristic (ROC) curve analysis to determine the optimal IVC-CI cutoff and multivariate logistic regression to identify independent predictors of mortality. Among 80 enrolled patients, in-hospital mortality was 31.3% (25/80). Non-survivors had a significantly lower mean IVC-CI (28.4% ± 9.1 vs. 52.7% ± 12.3, p<0.001). An IVC-CI ≤35% was the optimal cutoff (AUC 0.91) for predicting mortality, with 84% sensitivity and 89% specificity. In multivariate analysis, IVC-CI ≤35% was a strong independent predictor of mortality (adjusted OR 15.4, 95% CI: 4.8–49.2, p<0.001). A reduced IVC collapsibility index (≤35%) at admission is a potent, independent predictor of in-hospital mortality in severe acute decompensated heart failure. Bedside IVC assessment is a valuable, non-invasive tool for early risk stratification in this high-risk population. CBMJ 2026 January: vol. 15 no. 01 P:233-239